„The Ancient Lithuanian Calendar" by M. Gusev - Baltrūnas, Aleksandras (Lietuvos matematikos rinkinys, 1997)
The symbols of number in the ancient Lithuanian Calendar described by M. Gusev were investigated in this paper. It is proved that these symbols are original.